2022
DOI: 10.1002/jmri.28414
|View full text |Cite
|
Sign up to set email alerts
|

Application of Neuromelanin MR Imaging in Parkinson Disease

Abstract: MRI has been used to develop biomarkers for movement disorders such as Parkinson disease (PD) and other neurodegenerative disorders with parkinsonism such as progressive supranuclear palsy and multiple system atrophy. One of these imaging biomarkers is neuromelanin (NM), whose integrity can be assessed from its contrast and volume. NM is found mainly in certain brain stem structures, namely, the substantia nigra pars compacta (SNpc), the ventral tegmental area, and the locus coeruleus. Another major biomarker … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 99 publications
0
19
0
Order By: Relevance
“…To the best of our knowledge, we have presented the first, fully-automatic method for the segmentation of N1, which is a very promising biomarker for the early diagnosis of PD (Chau et al, 2020;Cheng et al, 2020;He et al, 2021He et al, , 2022Jokar et al, 2023). Indeed, recent studies have shown the potential of the N1 sign as a PD biomarker, as the loss of this sign has been associated with higher iron content in that area (Cheng et al, 2020), and PD patients with the highest iron content usually present bilateral loss of the N1 sign (He et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, we have presented the first, fully-automatic method for the segmentation of N1, which is a very promising biomarker for the early diagnosis of PD (Chau et al, 2020;Cheng et al, 2020;He et al, 2021He et al, , 2022Jokar et al, 2023). Indeed, recent studies have shown the potential of the N1 sign as a PD biomarker, as the loss of this sign has been associated with higher iron content in that area (Cheng et al, 2020), and PD patients with the highest iron content usually present bilateral loss of the N1 sign (He et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…We acknowledge some limitations in our study. Currently, most studies aiming at quantifying iron content through MRI utilize quantitative susceptibility mapping (QSM) rather than SWI (He et al, 2022). QSM models each voxel so that its intensity correlates with a physiological .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was based on magnetic sensitivity-weighted imaging (SWI), which has highly sensitive for detecting iron deposition area and its scope ( 7 ). Neuromelanin magnetic resonance imaging (NM-MRI) can better show the distribution of neuromelanin in the substantia nigra ( 8 , 9 ), and T2 * mapping can be used to quantify iron deposition ( 10 ). In this study, these three sequences were fused in pairs, and the substantia nigra was divided into the upper, middle, and lower regions for analysis and comparison.…”
Section: Introductionmentioning
confidence: 99%
“…
With great interest, I read the review article by He et al 1 As cited in page 8, we showed 2 that the contrast of "the locus ceruleus (LC) is associated with high water content." This observation of longer T1 and higher proton density in LC than in adjacent brain regions was confirmed by the authors as well.
…”
mentioning
confidence: 99%